Appendiceal knotting causing small bowel strangulation - Chandan Chatterjee; Suvashis Dash; Sahana Gupta; Shibajyoti Ghosh (Journal of Research in Medical Sciences, 2014)
Small bowel obstruction is a common cause of an emergency admission in the surgical wards. Acute appendicitis presenting with small bowel obstruction due to appendiceal knotting is a very rare and unsuspected condition in an emergency scenario. We report a case of acute small bowel obstruction in a 26-year-old male who, on exploration was found to have small bowel strangulation due to appendiceal knotting. Though rare, the possibilities of such a diagnosis should be kept in mind in patients with small bowel obstruction with no known identifiable etiology.